Response of gross primary productivity to compound dry and hot events in Inner Mongolia under large-scale circulation patterns - Yao Kang; Enliang Guo; Yongfang Wang; Gang Bao; Xiling Gu; Yuhai Bao; Naren Mandula; Cailin Wang (Global and Planetary Change, 2026)

3D porous cellulose/polyaniline aerogel composite as a high-performance electrode for selective electrosorption of rhenium - Ruichen Ma; Boxiao Zhao; Xiling Sun; Zhenning Lou; Junshuo Cui; Haibiao Yu; Yuejiao Wang; Weijun Shan; Xiaogeng Feng; Ying Xiong (Water Research, 2026)

Application of organic and inorganic acids in activating soil phosphorus in agriculture - Tong Luo; Huiping Gui; Nianchang Pang; Kai Peng; Qianqian Wang; Xiangru Wang; Xiling Zhang; Xiaoyan Ma (Applied Soil Ecology, 2026)

Optimizing partial nitrification-anammox in a membrane aerated moving bed biofilm reactor for mainstream nitrogen removal - Xiao Ran; Yulong Yang; Zhihong Zheng; Hongyu Wang; Xingyu Zheng; Xiling Peng; Jie Yao; Minhua Wei; Shuang Zhang; Jin Xu (Journal of Environmental Chemical Engineering, 2026)

Dietary fiber-bound polyphenols in Canavalia gladiata seed coat: Optimization of conditions, identification and bioactivity assessment of acid, alkaline, and enzymatic extraction - Yue Qiu; Jiayan Xie; Jing Liang; Jianhua Xie; Yi Chen; Xiaobo Hu; Nan Sun; Xiling Wang; Qiang Yu (Food Chemistry, 2026)

Infrared thermography-based behavior recognition: pedestrian skin temperature and thermal adaptive behaviors in outdoor activities for thermal comfort analysis - Xiling Lu; Jianlin Liu; Shaowen Wang; Yibo Teng; Yang He; Yun Su; Zhaosong Fang (Building and Environment, 2026)

Fertilization alters soil microbiome and root metabolites in grafted mulberry (Morus alba) with varied scion-rootstock combinations - Xin Chen; Haowen Fang; Yunfei Zhang; Zeyu Liu; Yingting Qin; Shuhang Cai; Jiayi Li; Lifu Zheng; Zhiwei Hou; Xiling Wang (Rhizosphere, 2025)

A preliminary study on estimating soil thickness on karst dolomite slopes using ground gamma radiation dose rate in Southwest China - Xinbao Zhang; Yuemin Yue; Liang Shi; Lu Wang; Shuai Yuan; Xiling Zhang; Mingming Sun; Yi Zeng; Yunqi Zhang; Hongyan Liu; Kelin Wang (CATENA, 2025)

The wheat HSF transcription factor TaHSFC3B confers drought tolerance through ROS scavenging and ABA pathway in transgenic Arabidopsis and wheat (Triticum aestivum L.) - Yaning Bu; Tianqi Song; Jianfei Zhou; Xinpeng Lei; Xiling Chang; Siyi Li; Yuxin Wang; Xiaoxing Wang; Ling Kang; Dongsheng Chen; Jishan Xiang; Xiaoke Zhang (Planta, 2025)

Chloride-enhanced degradation of micropollutants in natural water by the iron/biochar/peroxymonosulfate system: Role of iron(IV) and radicals - Mengqiao Zhang; Wenwen Gong; Xiling Wang; Lee Blaney; Guilong Peng; Virender K. Sharma (Journal of Hazardous Materials, 2025)

A high-hygroscopic, porous pH-colorimetric label based on κ-carrageenan and carboxymethyl cellulose composite cryogel for monitoring pork freshness - Yalu Yun; Xiling Cheng; Jin Xu; Yuxi Wang; Hailan Jin; Jian Li; Lijuan Wang (Food Hydrocolloids, 2025)

3-Oxo-11αH-germacra-1(10) E,4Z-dien-12,6α-olide, a sesquiterpene from Artemisia sieversiana, attenuates lipopolysaccharide-induced inflammation via NF-κB/MAPK pathways and oxidative stress via ROS pathway in RAW264.7 cells - Qianqian Ren; Lili Wang; Xin Wang; Xiaoran Min; Xiling Dai; Guozheng Huang; Jianguo Cao (Journal of Natural Medicines, 2025)

Single-helix inclusion formation of V-type starch-lutein: Investigation of structural, physicochemical, and in vitro release - Jiajun Song; Xianxiang Chen; Xiling Wang; Qiang Yu; Yi Chen; Mingyue Shen; Xinyu lv; Huiliang Wen; Jianhua Xie (Food Bioscience, 2024)

Multi-omics analysis reveals anthocyanin synthesis is associated with drought stress tolerance in Chaenomeles speciosa flowers - Shuangyu Zhang; Xiling Chen; Yanshen Ren; Xingyue Xue; Yaping Xu; Qi Wang; Yanru Xie; Tengxun Zhang; Jiayi Lin; Xiaolu Chen; Houhua Li (Journal of Cleaner Production, 2024)

Eco-friendly fabricating Tara pod extract-soy protein isolate film with antioxidant and heat-sealing properties for packaging beef tallow - Zihao Ren; Yuping Ning; Jin Xu; Xiling Cheng; Lijuan Wang (Food Hydrocolloids, 2024)

Chemical constituents of Pyrrosia davidii (Baker) Ching - Qian Wang; Xiaoxiao Pei; Xiling Dai; Quanxi Wang; Guozheng Huang; Jianguo Cao (Biochemical Systematics and Ecology, 2023)

Low Phosphorus Tolerance in Cotton Genotypes is Regulated by Root Morphology and Physiology - Asif Iqbal; Dong Qiang; Wang Xiangru; Gui Huiping; Zhang Hengheng; Zhang Xiling; Song Meizhen (Journal of Plant Growth Regulation, 2023)

Short-term residential exposure to air pollution and risk of acute myocardial infarction deaths at home in China - Jian Cheng; Hao Zheng; Jing Wei; Cunrui Huang; Hung Chak Ho; Shengzhi Sun; Dung Phung; Ho Kim; Xiling Wang; Zhongliang Bai; Mohammad Zahid Hossain; Shilu Tong; et al. (Environmental Science and Pollution Research, 2023)
Air pollution remains a major threat to cardiovascular health and most acute myocardial infarction (AMI) deaths occur at home. However, currently established knowledge on the deleterious effect of air pollution on AMI has been limited to routinely monitored air pollutants and overlooked the place of death. In this study, we examined the association between short-term residential exposure to China’s routinely monitored and unmonitored air pollutants and the risk of AMI deaths at home. A time-stratified case-crossover analysis was undertaken to associate short-term residential exposure to air pollution with 0.1 million AMI deaths at home in Jiangsu Province (China) during 2016–2019. Individual-level residential exposure to five unmonitored and monitored air pollutants including PM 1 (particulate matter with an aerodynamic diameter ≤ 1 μm) and PM 2.5 (particulate matter with an aerodynamic diameter ≤ 2.5 μm), SO 2 (sulfur dioxide), NO 2 (nitrogen dioxide), and O 3 (ozone) was estimated from satellite remote sensing and machine learning technique. We found that exposure to five air pollutants, even below the recently released stricter air quality standards of the World Health Organization (WHO), was all associated with increased odds of AMI deaths at home. The odds of AMI deaths increased by 20% (95% confidence interval: 8 to 33%), 22% (12 to 33%), 14% (2 to 27%), 13% (3 to 25%), and 7% (3 to 12%) for an interquartile range increase in PM 1 , PM 2.5 , SO 2 , NO 2 , and O 3 , respectively. A greater magnitude of association between NO 2 or O 3 and AMI deaths was observed in females and in the warm season. The greatest association between PM 1 and AMI deaths was found in individuals aged ≤ 64 years. This study for the first time suggests that residential exposure to routinely monitored and unmonitored air pollutants, even below the newest WHO air quality standards, is still associated with higher odds of AMI deaths at home. Future studies are warranted to understand the biological mechanisms behind the triggering of AMI deaths by air pollution exposure, to develop intervention strategies to reduce AMI deaths triggered by air pollution exposure, and to evaluate the cost-effectiveness, accessibility, and sustainability of these intervention strategies. Graphical abstract

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Flexible stretchable SEBS/n-alkane phase change composite films for highly efficient thermal management and infrared stealth applications - Yangjiu Zhao; Shaowei Shen; Xinya Wang; Ruirui Cao; Xiaoyong Jia; Xiling Niu; Haihui Liu; Xingxiang Zhang (Energy and Buildings, 2023)

Exposure to tris(2,6-dimethylphenyl) phosphate interferes with sexual differentiation via estrogen receptors 2a and 2b in zebrafish - Mengqiao Cui; Xiling Wu; Lei Yuan; Yue Zhai; Xin Liang; Zihan Wang; Jinhua Li; Lichun Xu; Weiyi Song (Journal of Hazardous Materials, 2023)

Urban-rural disparity in heatwave effects on diabetes mortality in eastern China: A case-crossover analysis in 2016–2019 - Junwen Tao; Hao Zheng; Hung Chak Ho; Xiling Wang; Mohammad Zahid Hossain; Zhongliang Bai; Ning Wang; Hong Su; Zhiwei Xu; Jian Cheng (Science of The Total Environment, 2023)

A comprehensive performance evaluation of the cement-based expanded perlite plastering mortar - Wu Yi; Zhou Xiling; Yang Jinglin; Wang Wenxuan; Tian Tian (Science of The Total Environment, 2023)

Effectiveness of Disinfectants Suitable for Inactivating SARS-CoV-2 at Cold-Chain Temperature - Xiaosong Wu; Yin Chen; Ling Wang; Xiling Guo; Lunbiao Cui; Yiming Shen; Fang Li; Hong Sun; Liubo Zhang; Jin Shen; Yan Xu (Food and Environmental Virology, 2022)

The mitochondrial genome of Mesocapnia daxingana (Plecoptera: Capniidae) - Ying Wang; Jinjun Cao; Weihai Li; Xiling Chen (Conservation Genetics Resources, 2017)

Minimal physiologically-based pharmacokinetic (mPBPK) model for a monoclonal antibody against interleukin-6 in mice with collagen-induced arthritis - Xi Chen; Xiling Jiang; William J. Jusko; Honghui Zhou; Weirong Wang (Journal of Pharmacokinetics and Pharmacodynamics, 2016)

Development of a Physiologically Based Pharmacokinetic Model to Predict Disease-Mediated Therapeutic Protein–Drug Interactions: Modulation of Multiple Cytochrome P450 Enzymes by Interleukin-6 - Xiling Jiang; Yanli Zhuang; Zhenhua Xu; Weirong Wang; Honghui Zhou (The AAPS Journal, 2016)

Deciphering the In Vivo Performance of a Monoclonal Antibody to Neutralize Its Soluble Target at the Site of Action in a Mouse Collagen-Induced Arthritis Model - Weirong Wang; Thomas S. McIntosh; Xiling Jiang; Rajitha Doddareddy; Elayne C. Dell; Honghui Zhou (Pharmaceutical Research, 2016)

Erratum to: Elevated Expression of Acid-Sensing Ion Channel 3 Inhibits Epilepsy via Activation of Interneurons - Qingqing Cao; Wei Wang; Juan Gu; Guohui Jiang; Xiling Bian; Kewei Wang; Zucai Xu; Jie Li; Guojun Chen; Xuefeng Wang (Molecular Neurobiology, 2016)

Identification and Expression Analysis of the 14-3-3 Gene Family in the Mulberry Tree - Yan Yang; Maode Yu; Fengxiang Xu; Yasheng Yu; Changying Liu; Jun Li; Xiling Wang (Plant Molecular Biology Reporter, 2015)

Antioxidative and Cardioprotective Effects of Total Flavonoids Extracted from Dracocephalum moldavica L. Against Acute Ischemia/Reperfusion-Induced Myocardial Injury in Isolated Rat Heart - Jiangtao Jiang; Xuan Yuan; Ting Wang; Hongmei Chen; Hong Zhao; Xinyan Yan; Zhiping Wang; Xiling Sun; Qiusheng Zheng (Cardiovascular Toxicology, 2014)

Initiation of dedifferentiation and structural changes in in vitro cultured petiole of Arabidopsis thaliana - Yang Yu; Zhenhua Feng; Guangchao Wang; Fei Li; Xiling Du; Jian Zhu (Protoplasma, 2010)